Peran Orang Tua dalam Pembelajaran Jarak Jauh pada Masa Pandemi Covid-19 di Madrasah Ibtidaiyah Muhammadiyah Cabang Purbalingga - Siti Marjiyah; Tutuk Ningsih (Jurnal Kependidikan)
This research was conducted to describe the role of parents in helping children do assignments during distance learning at MIM Purbalingga Branch. The research method used is descriptive qualitative. Collecting data through interviews, observation, and documentation with descriptive data analysis. The analysis technique that the researchers did was from data reduction, data presentation and conclusions. The results showed that parents have various roles in helping with children's tasks during distance learning. First, parents play a role in accompanying children. Both parents play a role in guiding the child. And the third parent plays a role in helping children work on assignments during distance learning at MIM Purbalingga Branch.